2011
DOI: 10.1163/156852811x588705
|View full text |Cite
|
Sign up to set email alerts
|

Senses of Dunamis and the Structure of Aristotle’s Metaphysics Θ1

Abstract: This essay aims to analyze the structure of Aristotle's Metaphysics Θ by explicating various senses of the term δύναμις at issue in the treatise. It is argued that Aristotle's central innovation, the sense of δύναμις most useful to his project in the treatise, is the kind of capacity characteristic of the pre-existent matter for substance. It is neither potentiality as a mode of being, as recent studies maintain, nor capacity for 'complete' activity. It is argued further that, in starting with the κύριος sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…6 Cf. Graham 1987, 184-185, Rist 1989, 106-107, Berti 1990, 47-51, Code 2003, 252, Makin 2006, xxviii, 133-135 and Burnyeat 2008 Many recent interpreters rely on Menn in support of their own arguments (e.g., Anagnostopoulos 2011, 412: "Menn (1994 has shown that in apparently early works, δύναμις and ἐνέργεια as a rule do not discriminate between activities that do, and those that do not, contain their ends"; Politis & Su 2015 rely heavily on Menn for their critical appraisal of Kosman's position. Cf.…”
mentioning
confidence: 99%
“…6 Cf. Graham 1987, 184-185, Rist 1989, 106-107, Berti 1990, 47-51, Code 2003, 252, Makin 2006, xxviii, 133-135 and Burnyeat 2008 Many recent interpreters rely on Menn in support of their own arguments (e.g., Anagnostopoulos 2011, 412: "Menn (1994 has shown that in apparently early works, δύναμις and ἐνέργεια as a rule do not discriminate between activities that do, and those that do not, contain their ends"; Politis & Su 2015 rely heavily on Menn for their critical appraisal of Kosman's position. Cf.…”
mentioning
confidence: 99%